ANALISIS PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KESULITAN BELAJAR SISWA - Afiatin Nisa (Jurnal Penelitian Bimbingan dan Konseling, 2017)
The aim of this study is to find out about the role of guiding and counseling teacher in overcoming the learning difficulties at M.Ts. Ar-Rahmah East Jakarta. The research method used in this study is descriptive qualitative. Source of the data are headmaster, guiding and counseling teacher, and 70 students of 7 grade. Instruments used in this study are questionnaire, interview guidelines, and observation guidelines.The findings show that the role of guiding and counseling teacher in helping and overcoming the learning difficulties of students of M.Ts. Ar-Rahmah East Jakarta in a Good Category. Key word: role, guiding and counseling teacher, learning difficulties